Polymyxin-induced neuromuscular weakness: a case report - Chin, Amanda X. Y.; Ng, Kay W. P.; Chan, Yee Cheun; Goh, Yihui; Rathakrishnan, Rahul (Frontiers in Neurology, 2024)
Polymyxin-induced neuromuscular blockade is a rare but potentially fatal condition, with majority of cases that were reported between 1962 and 1973. We describe a patient who developed hypercapnic respiratory failure after initiation of polymyxin for multi-drug resistant Escherichia Coli bacteremia, due to polymyxin-induced neuromuscular dysfunction. After cessation of polymyxin, he regained full strength, had complete resolution of ptosis, and was successfully extubated. In light of the renewed use of polymyxin in this era of antimicrobial-resistance, this case aims to raise awareness about this rare but life-threatening condition, which is easily reversible with early recognition and prompt discontinuation of the drug.